2021
DOI: 10.1186/s12903-021-01563-7
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to free flap surgery for maxillofacial reconstruction: focus on the submental island flap and the pectoralis major myocutaneous flap

Abstract: Background Microvascular tissue transfer (MTT) has been established as the gold standard in oral- and maxillofacial reconstruction. However, free flap surgery may be critical in multimorbid elderly patients and after surgery or radiotherapy, which aggravate microsurgery. This study evaluates indications and outcome of the submental island flap (SMIF) and the pectoralis major myocutaneous flap (PMMF) as alternatives to the free radial forearm flap (RFF). Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…3,5,[7][8][9]13,19,[21][22][23][24][25] However, some studies reported that patients in the pedicled flap group were significantly older than those in the free flap group. 4,16,26 In addition, the proportion of patients with ASA class I-II to those with ASA class III-IV was variably reported as lower, 4 similar, 5 or higher, 6,27 in the pedicled flap group compared with in the free flap group. Concerning disease characteristics, there were no differences in primary tumor location, T staging, and overall N staging, which are similar to those recorded in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,5,[7][8][9]13,19,[21][22][23][24][25] However, some studies reported that patients in the pedicled flap group were significantly older than those in the free flap group. 4,16,26 In addition, the proportion of patients with ASA class I-II to those with ASA class III-IV was variably reported as lower, 4 similar, 5 or higher, 6,27 in the pedicled flap group compared with in the free flap group. Concerning disease characteristics, there were no differences in primary tumor location, T staging, and overall N staging, which are similar to those recorded in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] There has been a recent resurgence of interest in the use of pedicled flaps in addition to the "workhorse" pectoralis major myocutaneous flap, including a submental island flap, temporalis myofascial flap, and supraclavicular island flap, which increases versatility in most of the head and neck defects. 4,6,10,11,[13][14][15][16] In addition, with the global strain on hospital resources during the COVID-19 pandemic, pedicled flaps can be a useful reconstruction in the current situation. 17,18 The purpose of the present study is to compare postoperative outcomes, including surgical complications, duration of hospital stay, hospital costs, and functional results in oral cavity cancer patients who underwent surgical resection followed by soft tissue reconstruction with a pedicled flap including pectoralis major myocutaneous, submental island, temporalis myofascial, and supraclavicular island flaps or a free flap including radial forearm and anterolateral thigh free flaps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, PMMF has a high success rate in clinical applications. Under the cases of patients receiving radiotherapy who encounter tissue contracture, large demand for flap tissue, patients undergoing secondary surgery who are unable to access available vessels, and challenging microsurgery, the PMMF is still an important candidate flap 25,26 . The significant difference in appearance scores between PMMF and FFF may be due to the fact that PMMF has less negative impact on the appearance of patients than FFF because the donor site is hidden, and the scar is not likely to be exposed.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative defects of oral cancer cause internal and external deformities of patients, which seriously affect their speech, swallowing and other functions 4,5 . Therefore, it is difficult for head and neck oncologists to completely remove oral tumors, immediately repair defects, restore the appearance and function of patients, reduce the physiological, psychological, and social impact on patients with oral cancer, and improve the quality of life 6,7 . Free flaps, such as anterior arm flap,…”
mentioning
confidence: 99%